A Red Flag: The Collapse of the Urban Chinese Medical Care System since the Economic Reforms of the early 1980s. - Bach, Aliza. (Tufts Archival Research Center, 2005)
The Urban Chinese Medical Care System has been in a state of decline starting with the economic reform period in mainland China in the early 1980s. In uncertain economic times, as state-owned enterprises and the corresponding social insurance declines, the government has withdrawn support from the medical care system. A combination of bureaucratic inefficiencies and lack of commitment has led to a decline in medical service provision as hospitals have sought out new, sometimes unethical ways to seek financing. Two diseases, Cancer and Viral Hepatitis, are explored to shed light on the existing system.